Co-morbidities and addictions affecting treatment outcome in new smear positive cases in Amritsar city, Punjab, India - Nagpal, Manisha; Devgun, Priyanka; Chawla, Naresh (International Journal Of Community Medicine And Public Health, 2016)
Background: Although the current approach to TB control focuses on case detection and treatment, recent studies suggest that this strategy might not be sufficient to achieve this goal and it may also be necessary to reduce risk factors that contribute to the occurrence of tuberculosis infection and/or disease. Such risk factors may act at one of several steps in the natural history of the disease. The life time risk of breaking down to disease among those infected with TB is 10–15%, which gets increased to 10% per year amongst those co-infected with HIV. Other determinants such as diabetes mellitus, smoking tobacco products, alcohol abuse and malnutrition also increase the risk of progression from infection to TB disease. Methods: The study was conducted on new smear positive patients registered under Directly observed treatment, short course (DOTS) in two Treatment Units (TUs) present in Amritsar city. The patients were enquired about their socio-demographic profile, family history, occupational history and associated co-morbidities and addictions. Data management and analysis was done by using Microsoft excel and SPSS version 17.00. Results: Out of 250 patients, 149 (59.6%) were males and 101(40.4%) were females. Male preponderance, with male to female ratio of 1.5:1 was seen. Out of the total 250 cases, 7.2% of the cases had associated diabetes mellitus, 1.2 % had hypertension and only 1 case was of asthma. While enquiring for addictions, it was observed that 28.8% of the cases were alcoholic, 17.2% were smokers, 8% had the habit of tobacco chewing and 6% were drug abusers. Favourable outcome was significantly higher in non-addicted cases while presence of co-morbidities was found to have no effect on the treatment outcome. Conclusions: In the present study, it was observed that favourable outcome was significantly associated with the absence of addictions. So, it is concluded that prevention of tuberculosis should include effective screening especially among high risk groups in order to ensure early detection and aggressive treatment.